Performance characteristics of respirable parallel particle impactors (PPI) - Mainelis, Gediminas; Han, Taewon T. (Journal of occupational and environmental hygiene, 2025)
Parallel Particle Impactors (PPIs) for respirable aerosols were introduced by SKC Inc. approximately 10 years ago and have been applied in the field; however, their collection efficiency curves have not yet been published. PPI consists of four impactors with different 50% cutoff sizes (d ) arranged in parallel, and their resulting performance is designed to follow the convention for respiratory aerosol sampling. This study investigated the collection efficiency curves and d values of disposable and reusable PPI models designed to operate at flow rates of 2, 4, and 8 L/min. The samplers were challenged with polydisperse sodium chloride (NaCl) particles and select sizes of polystyrene latex (PSL) particles. Bias maps and Bias Performance Criterion (BPC) values were calculated for challenge aerosols with mass median aerodynamic diameters (MMADs) ranging from 1 to 25 µm and geometric standard deviations (GSDs) ranging from 1.75 to 3.5. Results showed that 2, 4, and 8 L/min disposable PPI models had d values close to 4 µm, with minimal bias compared to an ideal respirable sampler, and an average BPC exceeding 95%. The reusable 2 L/min model also closely followed the respirable convention, with a d of 4.07 µm and a BPC of 100%. However, the d for the reusable 4 L/min and 8 L/min units was slightly higher, at 4.27 µm. ∼7% increase in the sampling flow rate to 4.3 L/min resulted in the d of ∼4 µm, with a BPC of 100%. Overall, the respirable PPI samplers, particularly their disposable models, show excellent adherence to the respirable aerosol sampling convention and contribute to the arsenal of tools for estimating exposures to respirable particles. The availability of PPI samplers operating at different flow rates offers flexibility in selecting a suitable sampler model based on available personal sampling pumps, anticipated concentrations of the respirable aerosol fraction, and desired sampling times.